Delivery of tanshinone IIA and α-mangostin from gold/PEI/cyclodextrin nanoparticle platform designed for prostate cancer chemotherapy. Issue 10 (15th May 2016) - Qiu, Shihong; Granet, Robert; Mbakidi, Jean-Pierre; Brégier, Frédérique; Pouget, Christelle; Micallef, Ludovic; Sothea-Ouk, Tan; Leger, David Y.; Liagre, Bertrand; Chaleix, Vincent; Sol, Vincent
Graphical abstract: Abstract: A new anti-cancer drug delivery system, based on gold nanoparticles, has been designed for hydrophobic active compounds. The system is a conjugate of gold/polyethyleneimine (AuNPs/PEI) nanoparticles and sulphated β-cyclodextrin (CD). Anionic cyclodextrin was attached to the positively charged AuNPs/PEI nanoparticles by ionic bonds. Tanshinone IIA and α-mangostin were extracted, purified and encapsulated into the AuNPs/PEI/CD nanoparticles. In vitro preliminary cell viability assays against prostate cancer cell lines PC-3 and DU145 showed that encapsulation resulted in increased cytotoxicity.